The British left and Zionism : History of a divorce - Kelemen, Paul (Book collections on Project MUSE., 2018)
The changes and divisions on the left over the Israel-Palestine conflict forms the central theme of this archive based study. While the Labour Party supported establishing a Jewish state in Palestine, as a modernising force, the communist movement opposed it, on the grounds that it facilitated imperial influence in the Middle East. In 1947, however, the British Communist Party rallied to the Zionist cause, leaving the Palestinian cause with no effective protagonists in Britain. The left's sympathy, at the time, was overwhelmingly with the Israeli state, considering its establishment a recompense to the Jewish people for the Holocaust. It was only after the 1967 Arab-Israeli War and Israel's occupation of the West Bank and Gaza, that the new left in Britain began to articulate a critical attitude to Israel and support for Palestinian nationalism. It is a perspective which has gradually gained ground in the political mainstream.